Species profiles life histories and environmental requirements of coastal fishes and invertebrates (South Atlantic)--Striped bass - Hill, Jennifer; Evans, James W.; Van Den Avyle, Michael J. (Washington, D.C. U.S. Department of the Interior, 1989)
U. S. Fish and Wildlife Service. Biological report ; 82(11.118)
Keywords: Striped bass--South Atlatic